Physical chemistry - Levine, Ira N. (New York : McGraw Hill Education, 1995)
This edition has been revised and updated. The author has added topics of current interest (in areas such as quantum chemistry and bioelectrochemistry), while retaining the coverage of thermodynamics and end-of-chapter problems.